Storm over Savannah The Story of Count d'Estaing and the Siege of the Town in 1779 - Piecuch, Jim (Georgia Open History Library, 1951)
Storm Over Savannah: The Story of Count d'Estaing and the Siege of the Town in 1779 tells the story of France's attempt to take down Savannah, the center for Britain's military power in the colonies in 1779. This mission, led by Charles-Henri, Comte d'Estaing, was taken on by four thousand troops of King Louis XVI, in cooperation with Americans. This account of the little-known Siege of Savannah reveals a dramatic story worth telling. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.